2021
DOI: 10.1029/2021sw002812
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the African and American Equatorial Ionization Anomaly (EIA) to 2014 Arctic SSW Events

Abstract: Previous studies have revealed that the variability in the ionosphere during Sudden Stratospheric Warming (SSW) events is connected to the coupling of the lower and upper atmosphere (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…For instance, the geomagnetic equator line is in the geographic NH in the African sector and in the geographic SH in the American sector. Very recently, Idolor et al (2021) stressed that the offsets are more in the American sector than in the African sector. Geometric configurations are related to the offsets, and they are more conspicuous in the American sector than in the African sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the geomagnetic equator line is in the geographic NH in the African sector and in the geographic SH in the American sector. Very recently, Idolor et al (2021) stressed that the offsets are more in the American sector than in the African sector. Geometric configurations are related to the offsets, and they are more conspicuous in the American sector than in the African sector.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Idolor et al. (2021) stressed that the offsets are more in the American sector than in the African sector. Geometric configurations are related to the offsets, and they are more conspicuous in the American sector than in the African sector.…”
Section: Discussionmentioning
confidence: 99%
“…The EEJ current is given by the following expression: where H HUA is the solar quiet (Sq) current computed for Huancayo and H PLU is the Sq current computed for the Piura magnetometer stations, respectively, while the estimated inferred vertical drift of the ΔH horizontal current was obtained from a mathematical relationship using the vertical drift model ). Anderson's quantitative mathematical formulation obtained from the neural regression technique is given by the following expression (Anderson et al, 2002;Yizengaw et al, 2014;Kassamba et al, 2020;Idolor et al, 2021;Idolor et al, 2022).…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…De Jesus et al (2017a) reported a nighttime enhancement in the TEC during the 2014 major SSW event in March. Both the SSW events (2013 and 2014) were also reported to overlap with the occurrence of geomagnetic storms (Idolor et al, 2021(Idolor et al, , 2022. Modeling results using the thermosphereionosphere-mesosphere-electrodynamics general circulation model (TIME-GCM) of the vertical drifts for the 2013 SSW event showed a significant increase in daytime vertical drift of ~100% associated with the moderate geomagnetic storm occurrence for the American sector (Maute et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation